Effects of Levetiracetam and Sulthiame on EEG in benign epilepsy with centrotemporal spikes: A randomized controlled trial. (March 2018) - Tacke, Moritz; Borggraefe, Ingo; Gerstl, Lucia; Heinen, Florian; Vill, Katharina; Bonfert, Michaela; Bast, Thomas; Neubauer, Bernd Axel; Baumeister, Friedrich; Baethmann, Martina; Bentele, Karl; Blank, Christian; et al.
Highlights: EEG data from a randomized controlled trial in children with BECTS. No significant differences between Sulthiame or Levetiracetam. Persistent EEG pathologies associated with an increased risk for recurrent seizures. Abstract: Purpose: BECTS (benign childhood epilepsy with centrotemporal spikes) is associated with characteristic EEG findings. This study examines the influence of anti-convulsive treatment on the EEG. Methods: In a randomized controlled trial including 43 children with BECTS, EEGs were performed prior to treatment with either Sulthiame or Levetiracetam as well as three times under treatment. Using the spike-wave-index, the degree of EEG pathology was quantified. The EEG before and after initiation of treatment was analyzed. Both treatment arms were compared and the EEG of the children that were to develop recurrent seizures was compared with those that were successfully treated. Results: Regardless of the treatment agent, the spike-wave-index was reduced significantly under treatment. There were no differences between the two treatment groups. In an additional analysis, the EEG characteristics of the children with recurrent seizures differed statistically significant from those that did not have any further seizures. Conclusion: Both Sulthiame and Levetiracetam influence the EEG of children with BECTS. Persistent EEG pathologies are associated with treatment failures.